THEMATIC PROGRESSION PATTERN : A TECHNIQUE TO IMPROVE STUDENTSâ WRITING SKILL VIEWED FROM WRITING APPREHENSION - Nurdianingsih, Fitri; Purnama, Yuniarta Ita (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
The objective of conducting this research was to find out : (1) whether or not the use of thematic progression pattern is more effective than direct instruction in teaching writing to the second semester students at English Education Department; (2) the students who have a low writing apprehension have better writing skill than those who have a high writng apprehension; and (3) there is an interaction between teaching technique and writing apprehension in teaching writing skill. This reasearch was an experimental research design. The population of this research was the second semester students at English Education Department of IKIP PGRI Bojonegoro. Meanwhile the sample of this research was selected by using cluster random sampling. The instruments of data collection were witing test and writing apprehension questionnaire. The findings of this study are: (1) thematic progression pattern is more effective than direct instruction in teaching writing; (2) the students who have low writing apprehension have better writing skill than those who have high writing apprehension; and (3) there is an interaction between teaching technique and writing apprehension in teaching writing skill. It can be summarized that thematic progression pattern is an effective technique in teaching writing skill at the second semester students of English Education Department in IKIP PGRI Bojonegoro. The effectiveness of the technique is affected by writing apprehension.